Relationship Between Science Process Skills and Multiple Intelligences among Senior High School Students in Biodiversity Learning - Apriliansyah, Muhammad Maulana Zakaria; Suhendar; Windyariani, Sistiana (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2025)
Background: This study aims to describe the profile of students' science process skills, the profile of high school students' multiple intelligences in biodiversity material, and to analyze the relationship between multiple intelligences and students' science process skills. Method: This study used a quantitative approach with a correlational method. The research subjects were 33 students in class X E MAN 1 Kota Sukabumi. Data collection was carried out using science process skills instruments and multiple intelligence instruments. Data analysis included descriptive statistics to describe the profile of each variable and inferential statistical analysis to determine the relationship between variables. Results The results showed that students' science process skills and multiple intelligences were in the moderate category. The correlation test results showed an r value of 0.236 with a significance of 0.186 (p > 0.05), which means that the relationship between multiple intelligences and science process skills was in the low category and not statistically significant. This indicates that multiple intelligences are not a dominant factor in determining students' science process skills, even though they have a positive relationship. This indicates that multiple intelligences do not have a significant influence on the level of students' science process skills. However, the positive correlation indicates that multiple intelligences contribute to the development of science process skills, even though they do not have a significant influence. Conclusion: These findings imply the need for learning strategies that are oriented towards scientific practice and differentiated learning according to students' intelligence characteristics. Keywords : Science process skills; multiple intelligences; biodiversity